2020
DOI: 10.1039/c9mh01394f
|View full text |Cite
|
Sign up to set email alerts
|

Preferred orientations of organic cations at lead-halide perovskite interfaces revealed using vibrational sum-frequency spectroscopy

Abstract: Using vibrational sum frequency generation (VSFG) spectroscopy, we investigate the behaviour of organic cations at the surface of a series of multilayer lead halide perovskite systems, finding that the behaviour of the organic cations changes dramatically close to the interface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 59 publications
0
13
0
Order By: Relevance
“…Such selection rules make SFG show powerful potential in the research of nanomaterials. In fact, SFG has been applied to probe molecular conformation of the organic cations of lead-halide perovskite 23 , 56 and the capping ligands on nanoparticle surfaces 24 , 25 , 30 .…”
Section: Resultsmentioning
confidence: 99%
“…Such selection rules make SFG show powerful potential in the research of nanomaterials. In fact, SFG has been applied to probe molecular conformation of the organic cations of lead-halide perovskite 23 , 56 and the capping ligands on nanoparticle surfaces 24 , 25 , 30 .…”
Section: Resultsmentioning
confidence: 99%
“…A Cs ion is spherical, so it does not break the crystallographic centrosymmetry of the system, so it is isotropic. In contrast, the MA cation is anisotropic and polar, so it can break the crystallographic symmetry of Pm m and induce polarization in the system if specific alignments of MA cations are assumed. Although it is reported that the MA cation in hybrid perovskite is in a rotationally disordered state at room temperature due to thermal motion of the cation, some evidence suggests that lattice distortions and local field effects permit preferential orientation of the MA cation at interfaces . For the study, we first determined the MA orientation in cubic MASnBr 3 .…”
mentioning
confidence: 99%
“…23−25 Although it is reported that the MA cation in hybrid perovskite is in a rotationally disordered state at room temperature due to thermal motion of the cation, 26 some evidence suggests that lattice distortions and local field effects permit preferential orientation of the MA cation at interfaces. 27 For the study, we first determined the MA orientation in cubic MASnBr 3 . Among different MA configurations, an MA cation placed along the diagonal of the cube is most energetically stable (Figure S1); this result agrees with a previous result.…”
mentioning
confidence: 99%
“…VSFG employs a broadband IR pulse (290 fs duration) centered at ~2850 cm -1 to excite CH vibrational modes of the SDS@2β-CD system, which is followed by a narrowband 1025nm near IR pulse to upcovert the vibrational coherence to a higher frequency macroscopic polarization emitted as the VSFG signal. As an even-order nonlinear optical process, only noncentrosymmetric systems produce VSFG responses, such as the air/liquid, air/solid and solid/liquid interfaces 29,31,[40][41][42][32][33][34][35][36][37][38][39] with a powerful demonstration of the techniques capabilities found in its application to the air/water interface. [43][44][45] Another class of systems that can be studied by VSFG that have not been paid much attention are materials without inversion centers.…”
Section: Linescanning Vsfg Imagingmentioning
confidence: 99%